Method for testing robust control quality for linear one-dimensional discrete control systems - Parshukov, Andrej N. (Вестник Томского государственного университета. Управление, вычислительная техника и информатика)
The article deals with one-dimensional linear control objects in discrete time. It is assumed that the opera-tors of the control object have structural and parametric inaccuracies in the description. In this paper, a criterion for the robust quality of control is obtained for a system consisting of a discrete control object with structural perturba-tions and a modal controller. Based on this criterion, a numerical method for checking the robust quality of control has been developed. The effectiveness of the method is illustrated by an example.